Congenital Syphilis Like Many Years Ago - Giulia Brighi; Giorgia Farneti; Antonella Marangoni; Elisabetta Tridapalli; Iria Neri; Maria Grazia Capretti; Giacomo Faldella (Case Reports in Infectious Diseases)
This case concerns a premature infant with typical signs of congenital syphilis born to an untreated foreign mother. Syphilis prevalence in pregnant women has been rising in Italy since the beginning of the 21st century, mainly due to immigration. A correct antenatal syphilis screening and consequent adequate therapy of pregnant woman are fundamental to prevent the neonatal infection.